If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5m + 9 = 34 Reorder the terms: 9 + 5m = 34 Solving 9 + 5m = 34 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 5m = 34 + -9 Combine like terms: 9 + -9 = 0 0 + 5m = 34 + -9 5m = 34 + -9 Combine like terms: 34 + -9 = 25 5m = 25 Divide each side by '5'. m = 5 Simplifying m = 5
| 4(2i-2)=80 | | X-3(2x-4)=-19 | | 9p=3p+18 | | 2(f-9)=102 | | (86+x)= | | 5bx-3=6x-c | | -200+25.00x=50 | | J-15=22 | | -200+25.00x=0.00 | | H+(9)=19 | | 9y=y+16 | | 45=5(p+4) | | 7x=157 | | 2x-3y=5x-6 | | R-2=15 | | 25y+21=5y+71 | | 3-2y=3x+7 | | y=8x^2-29-12 | | 3(3x+7)=102 | | 2(y-4)=6(y+2) | | -9(-2)+4f=7-3 | | 22x+3x=5 | | 10m-9=1 | | 5xn+2=17 | | 3(2y+1)=4(y+4) | | 6(v-6)-6=-3(-9v+8)-6v | | 9x+18=6x+63 | | 2h-19=8h-5 | | N+(39)=55 | | 3a*2b+ab*2-9ab= | | 8(13-18x)=-3064 | | 2h+19=8th-5 |